Nanoscale Block Copolymer Ordering Induced by Visible Interferometric Micropatterning: A Route towards Large Scale Block Copolymer 2D Crystals. (22nd November 2012) - Aissou, Karim; Shaver, Jonah; Fleury, Guillaume; Pécastaings, Gilles; Brochon, Cyril; Navarro, Christophe; Grauby, Stéphane; Rampnoux, Jean‐Michel; Dilhaire, Stefan; Hadziioannou, Georges
<x xml:space="preserve">Abstract</x> We have overcome the cost and time consumption limitations of common lithography techniques used to control the self‐assembly of block copolymers into highly ordered 2D arrays through the use of a guiding pattern created from a polymeric sub‐layer. The guiding pattern is a sinusoidal surface‐relief grating interferometrically inscribed onto an azobenzene containing copolymer sub‐layer leading to a defect‐free single grain of block copolymer domains. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>